150 local organizations and 10,000 farmers receive recommendations to manage joint COVID19 and climate risks in LAM - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS climate risk management approaches were retooled to help 150 institutions and 10,000 farmers mitigate both climate and COVID19 risks during 2020 across Latin America.